Teaching About Honesty Based on Characters Viewed From the Bible Perspective - Kilian Sirait; Nettina Samosir (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2026)
The Bible teaches much about wisdom. It could even be said to be a book of wisdom. One of the wisdoms it teaches is honesty. The biblical definition of honesty encompasses various aspects of human life, including relationships with oneself, others, and God. Given the breadth of the discussion on honesty, the author limits the discussion to the book of Proverbs, the person and teachings of Jesus, the writings of Paul, and the story of honesty in the life of Joseph. n the Bible, honesty is a highly emphasized moral value. Honesty is not merely about not lying, but also encompasses sincerity of heart, truthfulness in words and deeds, and integrity in all aspects of life. The Bible provides numerous examples and teachings about the importance of honesty, both in human relationships and in our relationship with God. Honesty is not only about avoiding lies, but also about doing what is right and according to God's will.